A discrete structure: FeSiAl/carbon black composite absorption coatings. (April 2017) - Duan, Yuping; Liu, Wei; Song, Lulu; Wang, Tongmin
Highlights: A kind of discrete structure was applied on coatings to improve the absorption performance. The effects of absorber content and structure on the absorption properties were studied. The absorption properties improved with the decrease of discrete patch size. The equivalent circuit model was constructed to analyze the improvement mechanisms of absorption properties. Abstract: We fabricated flaky FeSiAl (FFSA) absorption coatings and flaky FeSiAl (FFSA)/carbon black (CB) composite absorption coatings, and studied the effects of a discrete structure on the absorption performance of both coatings. The electromagnetic parameters of FFSA and CB were measured in the frequency range of 2–18 GHz using transmission/reflection technology. We also investigated the electromagnetic loss mechanisms of FFSA and CB. The microwave absorption properties of the coatings were determined by measuring the reflection loss (RL) using the arch method. We then analyzed the effects of the contents and the discrete structure on absorption properties. The results showed that, for the FFSA coatings, discrete structures markedly improved absorption properties. When the discrete unit sizes decreased, the absorption properties increased. The addition of CB further improved the absorption performance of the FFSA absorption coating. And when FFSA/CB composite coatings were cut into discrete structures, the absorption peak values decreased and the absorption peak frequencies shifted toward higher frequency ranges, which were consistent with those of the FFSA coating. Because of the conductivity differences between FFSA and CB, the FFSA/CB composite coatings with discrete structures had significant improvements in absorption. The improved absorption weakened when the CB content achieved a certain value. The equivalent circuit models were built to analyze the improvement mechanisms of absorption properties when the coating was cut into a discrete structure.